Nutrients Release from a Novel Gel-Based Slow/Controlled Release Fertilizer - H. Ding; Y. S. Zhang; W. H. Li; X. Z. Zheng; M. K. Wang; L. N. Tang; D. L. Chen (Applied and Environmental Soil Science)
A novel gel-based slow/controlled release fertilizer (G-CRF) was developed, which was produced by combining various natural, seminatural, and/or synthetic organic macromolecule materials and natural inorganic mineral with conventional NPK fertilizers. Its nutrient release characteristics were studied to compare with conventional fertilizers through the soil column leaching method. The influences of soil factors, including temperature, pH, water, and nutrient contents in the G-CRF on nutrient release, were also investigated through soil-water incubation method. These results indicated that the G-CRF had better effect on controlling release of N, P, and K nutrients, and the effect was more efficient when soil-water content was lower than 45% (w/w), temperature was below 35°C, and soil pH was in the range from weak acid to neutral. In addition, considering the effect of controlling nutrient release and cost of the materials in the G-CRF, it is recommended that the most feasible NPK nutrient contents in the G-CRF ranged from 30 to 35%.